Availability of the Yellow Fever Vaccine in Primary Health Care Services in Brazil - Hermsdorf, Marina Oliveira; da Silva, Tércia Moreira Ribeiro; Lachtim, Sheila Aparecida Ferreira; Matozinhos, Fernanda Penido; Beinner, Mark Anthony; Vieira, Ed Wilson Rodrigues (Frontiers in Tropical Diseases, 2022)
Objectives To analyze the availability of the Yellow Fever (YF) vaccine at Primary Health Care (PHC) services located in areas with vaccine recommendation in Brazil between two different periods. Methods Secondary data from the Program for Improving Access and Quality in PHC, with 13,666 services in 2013-14, and 19,125 in 2017-18, were used. A structured questionnaire was used for the data collection. Pearson’s chi-square and thematic cartographic maps were used to analyze the frequency of the YF vaccine, and Poisson regression with robust variances was used to analyze the associated factors. Results The overall frequency of PHC facilities with YF vaccine always available increased from 87.0% (CI 95%; 86.4-87.5) in 2013-14 to 89.7% (CI 95%; 89.2-90.1) in 2017-18. Facilities located in the South, Southeast, Midwest and Northern regions and in non-state capitals, as well as centers that had adequate facilities for vaccination actions, as well as an adey -50quate cold chain network, showed a greater prevalence of YF vaccine always available. Conclusion The frequency of a steady supply of YF vaccine available at PHC facilities, located in Areas with Routine Vaccination Recommendations, increased between 2013-14 and 2017-18. Geographical and structural characteristics related to vaccine actions at PHC facilities influenced access. The effective supply chain networks for the YF vaccine, together with adequate services at PHC facilities are essential to ensuring that the YF vaccine is always available.